Leaching of a polymetal gold ore and reducing cyanide consumption using cyanide-glycine solutions. (15th March 2021) - Barani, Kianoush; Dehghani, Morteza; Azadi, M.R.; Karrech, Ali
Highlights: Au and Cu leaching from a polymetal gold ore by glycine-cyanide were investigated. 80% Au and 5.5% Cu dissolved in 1500 ppm cyanide solutions over 72 h. 80% Au recovery could be obtained by 0.5 M/L glycine using 200 ppm cyanide. At the optimal approach, cyanide consumption can be reduced by about 80%. Abstract: Many aspects of gold ores leaching by glycine (C2 H5 NO2 ) and glycine-cyanide solutions are still not well understood. The base-metal components have been shown to have a strong impact on gold leaching kinetics. In this research, with the aim of reducing cyanide consumption, leaching of a polymetal (Pb-Cu-Zn) gold ore using a synergistic lixiviant mixture of cyanide and glycine has been studied. The results showed that by increasing cyanide concentration from 500 to 1500 ppm, the gold dissolution increased from 46% to about 80%. The gold dissolution of 90% could be achieved by adding 0.5–1 M/L glycine to 500 ppm cyanide while the copper dissolution increases to more than 30%. Interestingly, 80% gold dissolution could be obtained by 0.5 M/L glycine even using 200 ppm cyanide over 72 h. At the optimal approach, cyanide consumption can be reduced by about 80% compared with 1500 ppm cyanide (without glycine). In the studied sample, besides Cu, Pb, Zn and Fe minerals are the other cyanide consumers. Their dissolutions increased as glycine concentration increased. This can be considered as a negative aspect of the cyanide-glycine leaching and indicates its poor selectivity for gold. Pb, Zn, Fe, Ag, and Cu are more sensitive to glycine concentration rather than cyanide concentration.